1999
DOI: 10.1152/ajpheart.1999.276.6.h1927
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Akt/protein kinase B after stimulation with angiotensin II in vascular smooth muscle cells

Abstract: Involvement of Akt/Protein kinase B (PKB), a serine/threonine kinase with a pleckstrin-homology domain, in angiotensin II (ANG II)-induced signal transduction was investigated in cultured vascular smooth muscle cells (VSMC). Stimulation of the cells with ANG II led to a marked increase in the kinase activity of Akt/PKB, which coincided with Ser-473 phosphorylation. ANG II-stimulated Akt/PKB activation was rapid, concentration dependent, and inhibited by the AT1-receptor antagonist CV-11974, but not by pertussi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
79
2
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 54 publications
7
79
2
1
Order By: Relevance
“…Akt/PKB has been shown to be activated by factors that stimulate PI 3 kinase, including insulin-like growth factor, nerve growth factor, platelet-derived growth factor, and vascular endothelial growth factor (a number of receptor tyrosine kinases), Ang II (G-protein-coupled receptors), and insulin (60 -62). Interestingly, Ang II has recently been reported to activate Akt2/PKB in a PI 3 kinase-independent but arachidonic aciddependent and redox-sensitive signaling pathway (41,(63)(64)(65)(66). Taken together, these data suggest that activation of Akt2/ PKB is not only dependent on PI 3 kinase activation but also on reactive oxygen species signaling pathways.…”
Section: Hypertrophic Effects Of the Glp Gene In Irptcs-irptcsmentioning
confidence: 84%
See 1 more Smart Citation
“…Akt/PKB has been shown to be activated by factors that stimulate PI 3 kinase, including insulin-like growth factor, nerve growth factor, platelet-derived growth factor, and vascular endothelial growth factor (a number of receptor tyrosine kinases), Ang II (G-protein-coupled receptors), and insulin (60 -62). Interestingly, Ang II has recently been reported to activate Akt2/PKB in a PI 3 kinase-independent but arachidonic aciddependent and redox-sensitive signaling pathway (41,(63)(64)(65)(66). Taken together, these data suggest that activation of Akt2/ PKB is not only dependent on PI 3 kinase activation but also on reactive oxygen species signaling pathways.…”
Section: Hypertrophic Effects Of the Glp Gene In Irptcs-irptcsmentioning
confidence: 84%
“…This decrease in p27 kip1 appears to be critical in enabling the cells to enter the cell cycle. Cellular p27 kip1 levels have been shown as an indicator of cellular hypertrophy in VSMCs (40) and murine and rat proximal tubular cells (63)(64)(65). Furthermore, p27 kip1 regulates growth arrest in response to transforming growth factor, rapamycin, and contact inhibition.…”
Section: Hypertrophic Effects Of the Glp Gene In Irptcs-irptcsmentioning
confidence: 99%
“…11,35,36 Recently, 2 groups demonstrated that Ang II also stimulates Akt serine-threonine kinase. 13,14 Furthermore, Ozes et al 12 showed that Akt is essential in TNF-␣-induced activation of NF-B. PDTC is a potent inhibitor of NF-B.…”
Section: Discussionmentioning
confidence: 99%
“…11 Recently, Ozes et al 12 showed that Akt/protein kinase B (Akt) is essential in tumor necrosis factor-␣ (TNF-␣)-induced activation of NF-B. Takahashi et al, 13 as well as Ushio-Fukai et al, 14 have demonstrated Akt activation by Ang II, which may involve ROS. Activation of Akt NF-B activates numerous genes, including interleukin (IL)-1, IL-6, IL-8, interferon-␥, TNF-␣, intercellular adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1 (VCAM-1), and the chemokine MCP-1 (monocyte chemoattractant protein-1).…”
mentioning
confidence: 99%
“…However, the involvement of other upstream or parallel pathways has not been fully elucidated. Interestingly, the hypertrophic hormone angiotensin II is also a major stimulus for NAD(P)H oxidase, (17) with the latter occurring through a signaling cascade involving the activation of phosphatidylinositol 3-kinase (PI3K), the mammalian target of rapamycin (mTOR) and its downstream effector the 70-kDa ribosomal protein S6 kinase (p70 S6k ) (18,19). Recent data has also suggested that ROS are able to activate the extracellular regulated kinase 1/2 (ERK1/2) signaling pathway (20), glycogen synthase kinase-3β (GSK-3β) (21), a protein involved in the regulation of cell growth, and the phosphatase, phosphatase and tensin homolog (PTEN) which has been implicated in playing an important role in cardiac hypertrophy (22,23).…”
Section: Introductionmentioning
confidence: 99%